Analisis Proses Pemerolehan Bahasa pada Anak Usia 5 Tahun - Azizah, Lintang Nur; Indah Yunita, Marsya; Lidiyawati, Sabrini; Fauziyatul Muzakkiyah, Dela; Fauziah , Muhardila (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is about the process of knowing children's language acquisition at the age of 5 years. The aim of this research is to describe and analyze children's language acquisition either through interaction with parents or the surrounding environment. This research uses qualitative research methods because this research presents research results based on facts, namely by direct observation. The data obtained is the result of research using direct observation techniques with children and interviews with the children's parents. This research indicates that children have difficulty pronouncing Consonant letters such as R. Parents and the environment around children are important factors that influence children's language development. The interaction between children and their parents and their environment clearly has an influence on how children acquire language